Students’ View on Germany Literature Class by Video Assignment Project During Pandemic Covid-19 - Ellychristina D. Hutubessy (AL-ISHLAH: Jurnal Pendidikan, 2021)
Online learning during the COVID-19 pandemic requires technological media that can be used to achieve learning goals. The use of learning media must also be adapted to the needs of students and the current learning environment. The purpose of this study was to obtain student views on the German Literature class through a video assignment project. This study used a qualitative approach to examine the phenomena that occur in the field. Data were collected through questionnaires, observations, documents, and interviews. The data analysis technique used data reduction, data presentation and concluding. The results of the study concluded that students showed a positive attitude towards the use of video assignments for the Literature class, students have a high and stable level of concentration, and students can improve communication skills because the learning process can be done out of online class. It gave implications for the understanding of teaching staff about the appropriate technology media used for each course that is by the student's background and learning environment